Intracaval Migration of Ureteral Stent. Issue 1 (15th September 2015) - Hajji, M.; Bennani, M. S.; Bekkali, S.; Jroundi, L.
Ureteral stents have proven to be an invaluable tool for endourologists. Morbidity is minimal, but complications do exist. Up to 3 months complications are not frequent, but longer indwelling times are associated with increasing frequency of incrustation, infections, secondary stone formation, obstruction of the stented tract and migration. We report a rare case of a 33 year old pregnant patient with migration of an ureteral endoprosthesis. The patient received a right ureteral stent at 12 weeks for acute obstructive pyelonephritis. When her urologist tried to remove the ureteral stent post delivery, the stent was not found in the bladder. Ureteroscopy was performed but no ureteral stent was found. The patient showed a moderate improvement of the pyelonephritis, but complained about insidious palpitations. A CT scan was performed and showed the presence of the ureteral stent extending from the inferior vena cava up to the right atrium. Endovascular retrieval was performed through a puncture of the common femoral vein, using a curved guide that was introduced through the vena cava into the right atrium. Under fluoroscopic control, it was twisted around the stent and pulled out. The outcome was favorable, and no other complications were noted.